2009
DOI: 10.1007/s10549-009-0631-7
|View full text |Cite
|
Sign up to set email alerts
|

GPR30 and estrogen receptor expression: new insights into hormone dependence of inflammatory breast cancer

Abstract: Background-GPR30 is a novel G protein-coupled estrogen receptor (ER) associated with metastases in breast cancer (BC) and poor survival in endometrial and ovarian tumors. The association of GPR30 expression with inflammatory breast cancer (IBC), an aggressive and commonly hormone-independent form of BC, has not been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 34 publications
10
59
1
Order By: Relevance
“…The cross-talk between GPER-1 and EGFR is associated with activation of completely different signalling pathways [5,6,23] and could be responsible for the observed difference in survival rates. In agreement with the results obtained by us in the present study we have recently found that GPER-1 is associated with better patient survival in breast cancer patients [18] and have been recently confirmed for inflammatory breast cancer [24]. In accordance to expressional analyses, in vitro studies revealed controversial results regarding cellular functions of GPER-1.…”
Section: Discussionsupporting
confidence: 92%
“…The cross-talk between GPER-1 and EGFR is associated with activation of completely different signalling pathways [5,6,23] and could be responsible for the observed difference in survival rates. In agreement with the results obtained by us in the present study we have recently found that GPER-1 is associated with better patient survival in breast cancer patients [18] and have been recently confirmed for inflammatory breast cancer [24]. In accordance to expressional analyses, in vitro studies revealed controversial results regarding cellular functions of GPER-1.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, high levels of expression of GPER1 in breast, endometrial, and ovarian tumors have been associated with a higher risk of developing metastatic disease and poor survival (Prossnitz & Barton 2011). Moreover, high levels of GPER1 were identified in inflammatory breast cancer (IBC), an aggressive and commonly hormone-independent form of breast cancer (Arias-Pulido et al 2010). Recently, the overexpression of GPER1 and its plasma membrane localization have been suggested to be critical events in breast cancer progression, whereas the lack of GPER1 in the plasma membrane was associated with excellent longterm prognosis in ESR1-positive (Sjöström et al 2014) tamoxifen-treated breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a previous extensive survey, GPR30 was found to be highly expressed and significantly associated with tumor size (>2 cm), with the presence of distant metastases and increased human EGFR-2 (HER-2)/neu expression (24). Likewise, in a recent study performed in the aggressive inflammatory breast cancer, the majority of tumors were GPR30 positive (25), indicating that GPR30 expression may be considered a predictor of an aggressive disease. Recently, we have found that one of the strongest genes induced through GPR30, such as CTGF, is required for both proliferation and migration in ER-negative SkBr3 breast cancer cells (26).…”
Section: Introductionmentioning
confidence: 87%